أهداف التنمية المستدامة لأجندة 2030 قبل وبعد جائحة كورونا دراسة حالة الدول العربية - غالم, الهام (جامعة الوادي - University of Eloued, 2021)
جاءت الدراسة لتقديم حصاد لمستويات تجسيد اهداف التنمية المستدامة قبل وبعد جائحة كورونا، وذلك بالاستعانة بمؤشرات تعكس تداعيات الازمة على قدرة الدول العربية في تحقيق الأهداف المسطرة في اجندة التنمية المستدامة 2030 في ظل الأوضاع السائدة، كما هدفت الدراسة الى استعراض حزمة من الاليات والبرامج الواجب تبنيها للتخفيف من انعكاسات الازمة على الأهداف الاقتصادية والاجتماعية والبيئية والتنموية للدول العربية، وخلصت الدراسة الى ان جائحة كورونا لم تقتصر على الجوانب الصحية بل كانت لها تأثيرات سلبية على اهداف التنمية المستدامة بكل جوانبها ،فوجب على اثرها اتخاذ تدابير وبرامج لاحتواء التراجع في وتيرة إنجاز الأهداف المبرمجة بالإضافة الى إعادة النظر في جدولة مجمل الأهداف بما يتناسب والوضع الحالي ،واضافة بنود تتكفل بجانب الازمات وسبل إداراتها للحد من تداعياتها. The study came to present a harvestof the sustainable development goals before and after the The Corona pandemic, using indicators that reflect the repercussions of the crisis on the ability of Arab countries to achieve these goals. The study also aimed to review the mechanisms and programs necessary to mitigate the repercussions of the crisis on the economic, social, environmental and development goals of the Arab countries, The study concluded that the The Corona pandemic was not limited to health aspects, but had negative impacts on the sustainable development goals in all its aspects, and that measures must be taken to develop programs to contain the decline in the pace of achieving the programmed goals, in addition to rescheduling the overall goals in proportion to the current situation, and adding Items that take care of crises and ways to manage them to reduce their repercussions
The Sustainable Development Goals of the 2030 Agenda before and after the Corona pandemic,Case Study Arab Countries
مقال
Keywords: التنمية المستدامة ; جائحة كورونا ; مؤشرات التنمية المستدامة 2030